Museus, liberalismo e indústria cultural - Myrian Sepúlveda dos Santos (Ciências Sociais Unisinos)
This article analyzes cultural practices developed by museums in different periods in order to understand the different dimensions of the institutions and the contradictions inherent in them. Initially, it highlights the social role of museums in reinforcing the national-popular imaginary in the '1930s, in the postwar period and during the military dictatorship. Then is discusses the intertwinement between museums and the laws of the market, as well as their economic potential as they fulfill functions of social inclusion and strengthening of particular identities. The main question is about the possibility of coexistence between the museum's different dimensions and aesthetic values.